Read leadership books. Become a leader. - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Leadership books, be it biographies or self-help books, often present "leadership" as something achievable by any common person through diligence, skills, and, of course, luck, if only to sell the hope and magic that such power can sometimes come out of nothing. In 'How to Lead', author Jo Owen frames this 'luck' as 'context' – a meeting of 'skills' and 'performance' at the right place and at the right time.